AMP‐activated protein kinase inhibition in fibro‐adipogenic progenitors impairs muscle regeneration and increases fibrosis. Issue 1 (13th December 2022) - Liu, Xiangdong; Zhao, Liang; Gao, Yao; Chen, Yanting; Tian, Qiyu; Son, Jun Seok; Chae, Song Ah; de Avila, Jeanene Marie; Zhu, Mei‐Jun; Du, Min
Abstract: Background: Following muscle injury, fibro‐adipogenic progenitors (FAPs) are rapidly activated and undergo apoptosis at the resolution stage, which is required for proper muscle regeneration. When excessive FAPs remain, it contributes to fibrotic and fatty infiltration, impairing muscle recovery. Mechanisms controlling FAP apoptosis remain poorly defined. We hypothesized that AMP‐activated protein kinase (AMPK) in FAPs mediates their apoptosis during the muscle regeneration. Methods: To test, AMPKα1 fl/fl PDGFRα Cre mice were used to knock out AMPKα1 in FAPs. Following AMPKα1 knockout, the mice were injected with phosphate‐buffered saline or glycerol to induce muscle injury. Tibialis anterior muscle and FAPs were collected at 3, 7 and 14 days post‐injury (dpi) for further analysis. Results: We found that AMPKα1 deletion in FAPs enhanced p65 translocation to the nuclei by 110% ( n  = 3; P  < 0.01). AMPKα1 knockout group had a higher gene expression of MMP‐9 (matrix metalloproteinase‐9) by 470% ( n  = 3; P  < 0.05) and protein level by 39% ( n  = 3; P  < 0.05). Loss of AMPKα1 up‐regulated the active TGF‐β1 (transforming growth factor‐β1) levels by 21% ( n  = 3; P  < 0.05). TGF‐β promoted apoptotic resistance, because AMPKα1‐deficient group had 36% lower cleaved Caspase 3 (cCAS3) content ( n  = 3; P  < 0.05). Fibrotic differentiation of FAPs was promoted, with increased collagen protein level by 54% ( n  = 3; P  < 0.05). Moreover, obesity decreased phosphorylation of AMPK by 54% ( n  = 3; P  < 0.05), which decreased cCAS3 in FAPs by 44% ( n  = 3; P  < 0.05) and elevated collagen accumulation (52%; n  = 3; P  < 0.05) during muscle regeneration. Conclusions: These data suggest that AMPK is a key mediator of FAPs apoptosis, and its inhibition due to obesity results in fibrosis of regenerated muscle.